Direct Synthesis of N‐Heterocyclic Carbene‐Stabilized Copper Nanoparticles from an N‐Heterocyclic Carbene–Borane. Issue 49 (5th August 2019) - Frogneux, Xavier; Hippolyte, Laura; Mercier, Dimitri; Portehault, David; Chanéac, Corinne; Sanchez, Clément; Marcus, Philippe; Ribot, François; Fensterbank, Louis; Carenco, Sophie
Abstract: N‐Heterocyclic carbene (NHC)‐stabilized copper nanoparticles (NPs) were synthesized from an NHC–borane adduct and mesitylcopper(I) under thermal conditions (refluxing toluene for 2.5 h). NPs with a size distribution of 11.6±1.8 nm were obtained. The interaction between Cu NPs and NHC ligands was probed by X‐ray photoelectron spectroscopy, which showed covalent binding of the NHC to the surface of the NPs. Mechanistic studies suggested that NHC–borane plays two roles: contributing to the reduction of [CuMes]2 to release Cu 0 species and providing NHC ligands to stabilize the copper NPs. Abstract : Carbene‐stabilized NPs : N‐Heterocyclic carbene (NHC)‐stabilized copper nanoparticles (NPs, see figure) were synthesized in toluene from mesitylcopper and an NHC–borane reagent, which plays a dual role of contributing to the reduction of [CuMes]2 to release Cu 0 species and providing NHC ligands to stabilize the Cu NPs. The one‐step reaction is quantitative with respect to the copper precursor.